Assessing Geochemical Bioenergetics and Microbial Metabolisms at Three Terrestrial Sites of Serpentinization: The Tablelands (NL, CAN), The Cedars (CA, USA), and Aqua de Ney (CA, USA). Issue 6 (25th June 2021) - Cook, Melissa C.; Blank, Jennifer G.; Suzuki, Shino; Nealson, Kenneth H.; Morrill, Penny L.
Abstract: The subsurface process of serpentinization creates an extreme environment for microbial life. This environment includes reducing, ultra‐basic groundwater that is limited in electron acceptors. Despite these challenging conditions, there is a great deal of potential energy available to support microbial metabolisms both in the anaerobic subsurface and in aerobic surface environments where serpentinization associated groundwater discharges. In this study, the available energy was quantified through the calculation of chemical affinities, A r, for three sites of active serpentinization in North America: the Tablelands (NL, CAN), The Cedars (CA, USA), and Aqua de Ney (CA, USA). The results showed that A r values for each reaction were similar for all sites studied; however, the available energy varied a great deal from reaction to reaction. For example, the reaction of carbon monoxide oxidation provided the most energy to the system followed closely by hydrogen oxidation and methanotrophy. Potential microbial metabolisms were tested, simulating surface and subsurface conditions, in a laboratory‐based setting using microcosms with materials from each site. During these microcosm experiments, carbon monoxide oxidation was not observed, and there was little evidence of methane oxidation. Unexpectedly, microbial methanogenesis was observed in methane oxidation microcosms using material collected from The Cedars. The microbial production of methane occurred despite the addition of electron acceptors demonstrating the broad tolerance of methanogens at The Cedars for less reducing conditions. Plain Language Summary: Ultramafic rocks are iron and magnesium rich rocks that are predominant deep inside the Earth and on other planets and moons. Groundwater that flows through and reacts with these rocks produces conditions that may not be conducive to life because they lack oxygen, have little nutrients and very high pH values. However, these systems have a large amount of chemical energy available to support life. Based on chemical analyses of water and gases collected from field sites, we calculated the amount of potential chemical energy available at three groundwater spring locations with these extreme conditions. These calculations were then used to predict biological metabolisms that would use this energy. We tested our predictions through a series of laboratory experiments. Many of the metabolisms for which we tested were not observed, despite available energy in the system, while an unexpected metabolism, microbial formation of methane, prevailed. Key Points: Chemical affinities were calculated for key metabolic reactions at three terrestrial sites of serpentinization: the Tablelands (NL, CAN), The Cedars (CA, USA), and Aqua de Ney (CA, USA) Calculated chemical affinities predicted methane oxidation would occur at these sites; however, microcosm experiments showed little evidence of methanotrophy Microbial methanogenesis was inferred in microcosms from The Cedars